The Importance of Role Models in Predicting Adolescent Lifestyle: Evidence from the Lithuanian HBSC Study - Golambiauskas, Vladas; Žemaitaitytė, Monika; Koreivaitė, Jūratė; Šmigelskas, Kastytis (Psichologija, 2025)
Adolescence is a complex developmental stage characterized by risk-taking behaviours, identity formation, lifestyle choices, and the development of social relationships. Having a role model can influence adolescents’ choices toward either healthier or riskier behaviours. Therefore, this study, based on the Lithuanian HBSC survey, aimed to identify what kinds of role models adolescents have and how these role models predict their lifestyle choices. The study involved 6,628 students in grades 5–11 from 124 schools across Lithuania. The research assessed whether adolescents have role models (and their type) and how these role models predict lifestyle indicators in terms of sleep duration, physical activity (daily and vigorous), nutrition, smoking, alcohol use, and social media use. The results showed that the majority of adolescents (71%) reported having role models, most commonly family members (33%), friends (24%), social media celebrities (15%), athletes (12%), and TV stars (11%). Having a role model was most commonly associated with healthier lifestyle choices, particularly when the role model was a family member (more favourable sleep patterns, physical activity, and healthy eating indicators) or an athlete (more favourable physical activity and nutrition indicators). The least favourable role models were friends (associated with better physical activity and nutrition, but less favourable smoking and social media use indicators) and social media celebrities (associated with worse sleep and social media use indicators).